THE CONCEPTUALISATION OF THE CHALLENGES OF MODELS OF REGIONAL DESTINATION MANAGEMENT ORGANIZATIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The article examines the conceptual foundations and management challenges of regional Destination Management Organization (DMO) models. Tourism destination management is considered as a complex system of coordinated activities aimed at ensuring the sustainable development and competitiveness of tourism destinations. Particular attention is given to regional level DMOs, which operate as an intermediate governance level between national and local structures. The study analyzes the main strategic and substantive functions of regional DMOs and identifies their role in coordinating stakeholders and managing tourism development processes. Two main organizational models of regional DMOs are discussed: community-led and corporate-led models. The research highlights the main managerial challenges associated with these models, particularly political and financial dependencies that may affect the effectiveness and long-term sustainability of the organizations. It is concluded that despite institutional differences, regional DMOs face similar structural challenges that require balanced cooperation between public authorities and tourism industry enterprises. The study also notes that the manifestation of these challenges may vary depending on national governance systems, socio-cultural conditions, and levels of economic development.
Keywords: tourism destination; destination management organization (DMO); sustainable tourism; DMO models; regional DMO